Analisis Kemampuan Berpikir Kreatif Dalam Pemecahan Masalah Matematika Ditinjau Dari Adversity Quotient Pada Materi Fungsi Kuadrat - Silma Safira Hifyatin; Laila Hayati; Dwi Novitasari; Ketut Sarjana (Pendidikan Matematika FKIP Universitas Mataram, 2022)
This study aims to determine the mathematical creative thinking ability of MAN 2 Mataram students who have the adversity quotient of climber, camper, and quitter types in the quadratic function material. The type of research used is descriptive research with a quantitative approach. The research instrument used was an adversity quotient questionnaire, a mathematical creative thinking ability test, and an interview guide. The research sampling technique used purposive sampling, obtained by class XI IPA MAN 2 Mataram where 4 students with climber type adversity quotient, 23 students with camper type, and 5 students with quitter type. All students were given a mathematical creative thinking ability test, and from each type of adversity quotient, 2 students were taken for interview. The results of this study indicate that the creative thinking ability of students who have the climber type adversity quotient gets an average of 58.33 in the creative category. Furthermore, the mathematical creative thinking ability of students who have the adversity quotient of the camper type obtained an average of 36.59 with the category of being quite creative. And finally, the mathematical creative thinking ability of students who have an adversity quotient of the quitter type gets an average of 10.00 in the non-creative category.